Move Well, Live Well: A Preventive Epidemiology Approach to Musculoskeletal Health - Umy Yonaevy; Syarifah Syarifah; Ratih Prananingrum (Al-Hijrah Indonesia, 2026)
Background: Musculoskeletal disorders (MSDs) are among the leading causes of disability worldwide and continue to impose a substantial social and economic burden. Population aging, urbanization, and increasingly sedentary lifestyles have contributed to the increasing prevalence of MSDs. However, evidence on large-scale prevention strategies, particularly those applicable across diverse sociocultural contexts and low- and middle-income countries (LMICs), remains limited. Objective: This scoping review aimed to examine recent trends in the epidemiological burden of MSDs and identify effective community-based health promotion and prevention strategies reported in the contemporary literature. Methods: The scoping review was conducted following the PRISMA-ScR guidelines. Literature published between January 2020 and September 2025 was retrieved from Scopus, PubMed, and Google Scholar. After a systematic screening process, seven studies meeting the predetermined inclusion criteria were selected for descriptive and thematic analysis. Results: The reviewed evidence indicates a substantial and sustained increase in the global burden of musculoskeletal disorders (MSDs), reaching an estimated 1.686 billion cases in 2021 and projected to increase to 2.161 billion by 2035. Women of reproductive age and individuals in the productive working-age population (15–39 years) appear to be disproportionately affected. Key contributing factors include prolonged sitting, a sedentary lifestyle, and sustained static postures in educational and occupational settings. Interventions focused on ergonomics education, posture improvement, and physical activity promotion in schools and workplaces have consistently shown positive outcomes, including improved health literacy and healthier movement behaviors. Conclusion: The increasing burden of MSDs underscores the need to shift public health efforts from a treatment-oriented approach toward prevention and promotion strategies. The “Move Well, Live Well” framework emphasizes lifelong ergonomics education, workplace health promotion, and evidence-based policymaking. Early and interdisciplinary interventions in schools and workplaces can play a critical role in reducing future disability, increasing productivity, and supporting healthier communities.